Integrating Qur'anic worldview and natural science: a framework for Islamic secondary schools - Hassan, Nur Jannah (Zes Rokman Resources, 2018)
Islamic, modern and post-modern eras narrate how science and technology have borne impacts on humanity. Reacting against the challenges imposed by modern and post-modern tendencies, is the distinct global phenomenon of Islamic ―integrated education‖. But what constitutes as Islamically integrated science education? Analyses of various secondary school curricula, syllabi and textbooks of natural science implemented by a number of Islamic secondary schools that we visited in Malaysia and Indonesia, as well as in Brunei, Singapore, Southern Thailand, Mindanao and Ontario show very little integration if any. This article presents an integration framework for natural science, based on the Qur‘ānic notion of ―ūlū al-albāb‖ and Ghazālian discourse, especially on the qalb. Certain conventional aspects of natural science undergo holistic reposition, reinterpretation and reorientation from the Qur‘ānic worldview, whereby humanity's relationship with God, with itself and with the cosmos form the main constructs.